Molecular discrimination of sheep and cattle isolates of Echinococcus granulosus by SSCP and conventional PCR in Turkey - Simsek, Sami; Balkaya, Ibrahim; Ciftci, Ayse Turkan; Utuk, Armagan Erdem (Elsevier Science Bv, 2011)
Cystic echinococcosis (CE). caused by hydatid cysts, is a widespread and hazardous disease in humans and animals worldwide. The aim of the current study was to investigate the genetic characteristics of sheep and cattle isolates of Echinococcus granulosus obtained from eastern Turkey using Single Stranded Conformation Polymorphism (SSCP) analysis and conventional PCR method. A total of 54 isolates collected from Erzurum and Elazig provinces of east-Turkey were examined. The 31 of these were obtained from liver of sheep while 23 cattle isolates (12 of liver and 11 of lung) were tested. After the total genomic DNA isolation 12S rRNA gene of all isolates were examined by PCR for the aim of genetic characterization by conventional PCR and mitochondrial CO1 gene for SSCP analysis. The 12S rRNA-PCR yielded 254 bp of amplification product with all samples analyzed. Thus, these samples were identified as G1-G3 cluster (E. granulosus sensu stricto). At least two major single stranded bands were resolved for G1-G3 cluster and G5 in SSCP analysis. While the resolution of more than two additional single stranded bands in SSCP indicated the existence of G7 genotype. The SSCP analysis was identified the G5 and G7 while failed to G1 and G3. The present SSCP analysis classified all 54 cyst isolates from sheep and cattle as E. granulosus sensu strict (G1-G3 cluster). However, some sequenced samples for Cl and G3 showed the same band patterns by SSCP. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; SSCP; Cattle; Sheep; PCR; Genotype; Turkey